Bochum Assessment of Avoidance-based Emotion Regulation for Children (BAER-C): Development and evaluation of a new instrument measuring anticipatory avoidance-based emotion regulation in anxiety eliciting situations. - Michael W Lippert; Katharina Sommer; Tabea Flasinski; Jan Schomberg; Verena Pflug; Hanna Christiansen; Tina In-Albon; Susanne Knappe; Marcel Romanos; Brunna Tuschen-Caffier; Silvia Schneider (PLoS ONE)
Avoidance-based emotion regulation plays a central role in the development and maintenance of anxiety disorders across the life span. However, measures for children that account for different avoidance strategies, are scarce. Derived from Gross' Process Model of Emotion Regulation, the Bochum Assessment of Avoidance-based Emotion Regulation for Children (BAER-C) was developed to assess avoidance strategies (cognitive avoidance, behavioural avoidance, verbal reassurance, and social reassurance) and reappraisal in anticipatory anxious situations. In the present study, the BAER-C was administered to 129 school children aged 8 to 14 and 199 children with anxiety disorders aged 8 to 16 and their parents, along with established measures on anxiety, psychopathology, and emotion regulation. Factor structure, internal consistency, convergent, divergent and construct validity were analysed. Results of the anxious sample showed a satisfactory internal consistency (McDonald's ω = .94) for all scales as well as positive correlations with anxiety symptoms (all rs > .17, all ps < .05). Factor analysis supported a five-factor model. This model was confirmed in the student sample. Children with an anxiety disorder scored higher on behavioural avoidance, verbal reassurance, and social reassurance than school children (F (5,304) = 12.63, p = .003, ηp2 = .17). Results for construct validity were ambiguous. Our analyses suggest that the BAER-C is a promising theory-based new instrument to reliably assess different avoidance strategies in children. More research is needed to further analyse construct validity with other emotion regulation questionnaires.